Case Report: Gastric Wall Thickening: Radiological Diagnostic Challenges in Gastric Malignancy - Putu Ayu Winda Wirastuti Giri; Nyoman Srie Laksminingsih; Firman Parulian Sitanggang; I Gusti Ayu Sri Mahendra Dewi; I Wayan Juli Sumadi; Luh Putu Iin Indrayani Maker (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2021)
Gastric abnormalities show nonspecific gastrointestinal symptoms and similarly radiological findings. Intra and extra luminal gastric wall thickening are the most common finding in benign and malignant pathologic process. This aim of this case report was to describe several characteristics such as the location and size of the lesion, involvement of the gastric wall and surrounding structures, calcifications, and contrast enhancement pattern which can assist in radiological diagnosis. Several cases at our institution have similar gastrointestinal complaints, however, there were different lesions characteristic found in contrast enhanced abdominal CT scan. The first case 72-years-old man experienced hematemesis with radiologic finding diffuse gastric mucosal thickening as well as homogenous contrast enhancement but without calcification.  The second case 37-years-old man complaint dizziness and melena with radiologic finding large tumor more than 10 cm in size, amorph calcification and heterogenous contrast enhancement. The last 60-years-old man case experienced melena and hematemesis, from abdominal CT scan showed irregular gastric mucosal thickening with heterogenous contrast enhancement and fat stranding around the lesion, without calcification. Methods used in these cases were contrast-enhanced abdominal CT scan, esophagogastroduodenoscopy (EGD), and biopsy in order to determine the diagnosis. Contrast-enhanced abdominal CT scan plays a vital role in describing the lesion characteristics which affects the determination of treatment options and future prognosis.